Marine red algae of Pacific Mexico - Dawson, E.Y; Hollenberg, G.J (University Southern California Press, 1961)
Contents: Part 3. Cryptonemiales, Corallinaceae subf Melobesioideae. Part 4. Gigartinales. Part 5. The Genus Polysiphonia.